Desarrollo de un sistema de adquisición de datos para evaluar la calidad de energía en la Universidad Técnica de Cotopaxi Sede la Matriz. - Sánchez Masaquiza, Manuel Mesías (2023)
This technological proposal deals with the implementation of a Data Acquisition System (DAS) designed to evaluate and monitor power quality at the Technical University of Cotopaxi, specifically at its main campus, known as La Matriz. Power quality is a critical aspect in any institution, since it affects the proper functioning of equipment and electrical systems, which can lead to economic and efficiency losses. The design of the Data Acquisition System has been carried out considering the appropriate selection of sensors and measurement devices, which allow continuous and accurate monitoring and recording of the main power quality indicators, such as voltage, current, frequency, power factor, among others. The implementation of the ODS has involved the use of state-of-the-art technologies and the programming of specific algorithms for processing and analyzing the data obtained in real time. In addition, an intuitive and friendly user interface has been developed to facilitate access to information and visualization of results for authorized users. To validate the developed system, different tests and analyses were carried out in different load situations and conditions of the university's electrical network. The results obtained demonstrated the effectiveness and reliability of the Data Acquisition System in the evaluation of the quality in the University.